Survey of Labour and Income Dynamics, 2007 [Canada]: Cross-Sectional Census Family File ... : Cross-Sectional Census Family File ... - Statistics Canada. Household Surveys Division (Borealis, 2023)
The Survey of Labour and Income Dynamics (SLID) complements traditional survey data on labour market activity and income with an additional dimension: the changes experienced by individuals over time. At the heart of the survey's objectives is the understanding of the economic well-being of Canadians: what economic shifts do individuals and families live through, and how does it vary with changes in their paid work, family make-up, receipt of government transfers or other factors? The survey's longitudinal dimension makes it possible to see such concurrent and often related events. SLID is the first Canadian household survey to provide national data on the fluctuations in income that a typical family or individual experiences over time which gives greater insight on the nature and extent of poverty in Canada. Added to the longitudinal aspect are the "traditional" cross-sectional data: the primary Canadian source for income data and providing additional content to data collected by the Labour Force Survey ... : Notes: Persons over 16 years of age. All individuals in Canada, excluding residents of the Yukon, the Northwest Territories and Nunavut, residents of institutions and persons living on Indian reserves. Overall, these exclusions amount to less than 3 percent of the population.; ...